2014
DOI: 10.1007/s00468-014-1048-4
|View full text |Cite
|
Sign up to set email alerts
|

Topography influences the distribution of autumn frost damage on trees in a Mediterranean-type Eucalyptus forest

Abstract: Key messageExtreme temperatures are causing forest dieback in a Mediterranean-type forest. Topography and cold-air pooling explain the geographic distribution of frost dieback in susceptible tree species. AbstractAlterations to the frequency and intensity of extreme temperatures, predicted with climate change, pose a threat to the health of many forests. Some Mediterranean climate regions are experiencing higher temperature variability, including more extreme low and high temperature events. Following one such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…In a recent study, it was shown that a widespread mortality event in a tropical dry forest from Mexico was related to an unusual combination of duration, intensity, and timing of a frost event (Bojórquez, Álvarez‐Yépiz, Búrquez, & Martínez‐Yrízar, ). Similarly, dieback events related to frost injury were also reported for species from the Mediterranean region (Jalili et al, ; Matusick, Ruthrof, Brouwers, & Hardy, ). These examples illustrate well the impact of global warming on the vegetation, since its effects, especially the large temperature fluctuations, can significantly increase the vulnerability of forest species in virtually all biomes.…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 56%
“…In a recent study, it was shown that a widespread mortality event in a tropical dry forest from Mexico was related to an unusual combination of duration, intensity, and timing of a frost event (Bojórquez, Álvarez‐Yépiz, Búrquez, & Martínez‐Yrízar, ). Similarly, dieback events related to frost injury were also reported for species from the Mediterranean region (Jalili et al, ; Matusick, Ruthrof, Brouwers, & Hardy, ). These examples illustrate well the impact of global warming on the vegetation, since its effects, especially the large temperature fluctuations, can significantly increase the vulnerability of forest species in virtually all biomes.…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 56%
“…A positive relationship with the only significant wet season temperature variable, the lowest daily minimum (Jarrah ES, 0.009 and Marri ES, 0.024), possibly relates to the damaging effects of frost (Matusick et al . ). Alternatively, lower wet season overnight temperatures are often associated with dry periods with clear night skies, suggesting an indirect effect of soil moisture availability.…”
Section: Resultsmentioning
confidence: 97%
“…Lowland vegetation is in general more prone to freezing damage when advective frosts occur in agreement with recent studies in savannas in South Africa and Brazil (Hoffmann et al, ; Muller et al, ; Whitecross et al, ). This finding can be explained by the strong influence of elevation on temperature distribution at the regional and landscape level (Florinsky, Kulagina, & Meshalkina, ; Hummer‐Miller, ; Matusick, Ruthrof, Brouwers, & Hardy, ), driving the movement of cold air masses downhill during an advective frost (Kalma, Laughlin, Caprio, & Hamer, ; Lindkvist & Lindqvist, ). Accordingly, the historic cold wave that caused the February 2011 severe frost entered our study area from the adjacent northeastern mountains and drained into the lowlands where cold air remained for at least three consecutive days, leading to the widespread frost‐induced tree mortality episode.…”
Section: Discussionmentioning
confidence: 99%